Adult onset tic disorders. Issue 6 (1st June 2000) - Chouinard, Sylvain; Ford, Blair
Abstract : BACKGROUND: Tic disorders presenting during adulthood have infrequently been described in the medical literature. Most reports depict adult onset secondary tic disorders caused by trauma, encephalitis, and other acquired conditions. Only rare reports describe idiopathic adult onset tic disorders, and most of these cases represent recurrent childhood tic disorders. OBJECTIVE: To describe a large series of patients with tic disorders presenting during adulthood, to compare clinical characteristics between groups of patients, and to call attention to this potentially disabling and underrecognised neurological disorder. METHODS: Using a computerised database, all patients with tic disorders who presented between 1988 and 1998 to the movement disorders clinic at Columbia-Presbyterian Medical Center after the age of 21 were identified. Patients' charts were retrospectively reviewed for demographic information, age of onset of tics, tic phenomenology, distribution, the presence of premonitory sensory symptoms and tic suppressibility, family history, and associated psychiatric features. These patients' videotapes were reviewed for diagnostic confirmation and information was obtained about disability, course, and response to treatment in a structured follow up interview. RESULTS: Of 411 patients with tic disorders in the database, 22 patients presented for the first time with tic disorders after the age of 21. In nine patients, detailed questioning disclosed a history of previous childhood transient tic disorder, but in 13 patients, the adult onset tic disorder was new. Among the new onset cases, six patients developed tics in relation to an external trigger, and could be considered to have secondary tic disorders. The remaining patients had idiopathic tic disorders. Comparing adult patients with recurrent childhood tics and those with new onset adult tics, the appearance of the tic disorder, the course and prognosis, the family history of tic disorder, and the prevalence of obsessive-compulsive disorder were found to be similar. Adults with new onset tics were more likely to have a symptomatic or secondary tic disorder, which in this series was caused by infection, trauma, cocaine use, and neuroleptic exposure. CONCLUSIONS: Adult onset tic disorders represent an underrecognised condition that is more common than generally appreciated or reported. The clinical characteristics of adults newly presenting to a movement disorder clinic with tic disorders are reviewed, analysed, and discussed in detail. Clinical evidence supports the concept that tic disorders in adults are part of a range that includes childhood onset tic disorders and Tourette's syndrome.